Negotiating Narrative Identity in Intercultural Contexts - the Role of Applied Theatre - Heidi M. Haraldsen; Siri Ingul (Cappelen Damm Akademisk NOASP, 2017)
The aim of this study is to investigate how applied theatre can facilitate arenas and methods to support identity development particularly favorable to an intercultural context, explored through the concept of narrative identity. Identity and identity processes may be extra challenging to people with intercultural backgrounds. Research shows that how you master your identity affects how you master your life. A case study of two intercultural applied theatre projects was used to address the research question. The article builds on the experiences of two drama teachers and one teaching artist / artistic leader. The interpretation and analysis of the theory related to practice makes visible how aesthetic processes of negotiating and staging life stories (narratives), through applied theatre methods, facilitate participant's exploring, constructing, re-constructing and meta-reflecting own identity.